Odpowiedź :
2x+y=1
x-2y=8
y=1-2x
x-2(1-2x)=8
y=1-2x
x-2+4x=8
y=1-2x
5x=10
y=1-2x
x=2
y=-3
x=2
x-2y=8
y=1-2x
x-2(1-2x)=8
y=1-2x
x-2+4x=8
y=1-2x
5x=10
y=1-2x
x=2
y=-3
x=2
{2x+ y=1
{x-2y=8 /*(-2)
{2x+ y=1
{-2x+4y=-16
5y = -15
y = -3
x-2y=8
x = 2y + 8 = -6 + 8 = 2
{x = 2
{y = -3
{x-2y=8 /*(-2)
{2x+ y=1
{-2x+4y=-16
5y = -15
y = -3
x-2y=8
x = 2y + 8 = -6 + 8 = 2
{x = 2
{y = -3
2x + y =1
x-2y=8
y=1-2x
x-2y=8
y=1-2x
x-2(1-2x)=8
y=1-2x
x-2+4x=8
y=1-2x
5x=10 /5
y=1-2x
x=2
y=1-(2*2)
x=2
y=-3
x=2
x-2y=8
y=1-2x
x-2y=8
y=1-2x
x-2(1-2x)=8
y=1-2x
x-2+4x=8
y=1-2x
5x=10 /5
y=1-2x
x=2
y=1-(2*2)
x=2
y=-3
x=2